Collaborative Governance – Can it Achieve Sustainable Development Goals (SDGS) Towards Independent Villages in Strategic Border Areas - Sundari Nasution, Mimin; Zulkarnaini, Zulkarnaini; Tua Simanjuntak, Harapan (Indonesian Association for Public Administration (IAPA), 2023)
State borders are strategically important places. Because of this weakness, the border area as the country's front porch becomes a strategic issue. The border area of Indonesia, as the country's external face, is impressed if its management is based on a safety approach (safety belt method). Villages in Indonesia are still difficult to disentangle; it is frequently stated that he is lagging in development affairs, such that social, economic, infrastructure and other advances appear to be overlooked. The Village Sustainable Development Goals are a development concept that emphasizes ecologically responsible growth while also protecting local culture. The purpose of this research is to determine how the Sustainable Development Goals (SDGs) are implemented in the border communities of the Rokan Hilir region. A qualitative technique is used in this investigation. To acquire a thorough grasp of the research problem, data was gathered using in-depth interviews, observation, and interactive photographic techniques. Purposive sampling was used to identify informants. After collecting the data, it is processed using an analytical technique with the N-Vivo 12 to explain, show, and place the data so that conclusions can be reached. Cooperation in the three components of the SDGs is required to achieve sustainability, which balances development on the economic, social, and environmental dimensions. The study's findings indicate that the Village Sustainable Development Goals, particularly in Teluk Pulai Village in the border area of Rokan Hilir District, have not been realized based on indicators of sustainability fulfillment. Apart from that, it can be seen from the unmet SDGs performance targets, which had an impact on the Village SDGs Score of 35.96 and the Developing Village Index (IDM) with a Developing status. The SDGs goals in the border area have not been realized, including a lack of village development plans, which solely focus on satisfying the requirements of the village community, thus the SDGs Village goals required by the community are not planned.